Solid waste characterization in Ethiope East Local Government Area of Delta State, Abraka, Nigeria - Obiajulu Peretomode (Journal of Applied Sciences and Environmental Management, 2019)
On-site waste characterization was carried out on four dumpsites in Abraka municipality with standard methods used. Results obtained show that the mean composition of organic waste was significantly higher in station 1 (38.15±2.03) than other stations, while paper waste (18.97±0.43), glass waste (1.84±0.18), metal waste (3.03±0.12) and other miscellaneous wastes were significantly higher in station 2 than other stations. Plastic waste was significantly higher in station 4 (7.85±0.29) than other stations. Wastes disposed carelessly spread to the road and to surrounding water bodies. Community participation in waste disposal can be a catalyst in community development work, because it gives residents a feeling of self-esteem, generates income through recycling and reduce waste material transported for disposal.